Management of Educational Facilities and Infrastructure in Islamic Junior High School - Rizky, Diannisa; Karnati, Neti; Supadi, Supadi (Journal of Education Reseach and Evaluation, 2022)
In the era of globalization, education is one of the mainstays for preparing Indonesian human resources, especially in facing industry 4.0. One of the efforts to improve the quality of Indonesia's young generation is through the learning process in schools, and successful learning is supported by the effective and efficient utilization of all educational facilities and infrastructure in schools. This study aims to analyze the planning, procurement, inventory, maintenance, and removal of educational facilities and infrastructure at one of Islamic Junior High School. Qualitative research data collection techniques through observation, interviews, documentation, and triangulation. Data analysis techniques: data collection, data reduction, data presentation, and concluding. Based on the results of the study, it can be seen: first, planning activities for facilities and infrastructure are always carried out starting from analysis, determining funds, and selecting needed goods, second procurement activities are carried out by buying and determining funds as needed, but there are still procurement activities that have not been running, the three inventories are always carried out as evidence of the procurement of goods, and coding is carried out when the goods come to school, the fourth maintenance of facilities and infrastructure is carried out regularly by involving school residents and discussed through periodic meetings, fifth Deletion activities are carried out if there are inappropriate goods, damaged goods, and goods that are no longer used.